The endorsement and adoption of Muslim friendly hospitality training programme by Malaysia International Halal Academy, Jabatan Kemajuan Islam Malaysia White paper - Ramli, Noriah; Zawawi, Majdah; Abas, Afridah; Azmi, Ida Madieha (2019)
White paper submitted for the adoption and endorsement of Muslim friendly hospitality training programme by Malaysia International Halal Academy